Women, crime, and character: from Moll Flanders to Tess of the D'Urbervilles - Lacey, Nicola (Oxford Univ. Press, 2008)
'Don't go to murder my character': criminal responsibility in the age of Moll Flanders 1 -- 'What is the use of a woman's will?': the demise of Moll in the age of sensibility 51 -- 'The weaker half of the human family'?: responsibility, mind and morals in the age of Tess